Congenital tracheal stenosis associated with left pulmonary artery sling accompanied by tracheal diverticula: A case report - Samir Jabari; Arndt Hartmann; Robert Cesnjevar (Elsevier, 2017)
We present the case of an eleven-year-old boy with history of stridor since birth with suspicion of tracheal stenosis due to a vascular ring. CT-evaluation revealed a pulmonary artery sling (PAS) and complete tracheal rings with a long segment funnel type tracheal stenosis. Histopathological evaluation additionally revealed a septum within the stenotic part dividing the trachea into a stenotic left part and a right part which turned out to only be an evagination like a small diverticulum. The long segment tracheal stenosis was opened in the middle and an anterior-posterior tracheal sliding plasty was performed after resecting the diseased part of the obstructive cartilage. The patient was extubated on the third postoperative day and the stridor disappeared immediately. To the best of our knowledge, this is the first report of tracheal stenosis with a pulmonary artery sling accompanied with tracheal diverticulum.